Uso de fosfatos e vitamina C em dietas úmidas para cães na prevenção de odontólitos - Silveira, Moara Marina Belo Matos (2017)
Based on the importance of good oral health in dogs and its effect on the general animal health, this research trial aimed to evaluate the effect of inclusion of two different sources of phosphate and vitamin C in moist (or wet) commercial canine diets on dental plaque formation, depth gingival sulcus, and salivary pH in adult healthy dogs.The experiment was conducted at the Companion Animal Nutrition Research Center in the Department of Animal Sciences at the Federal University of Lavras, Lavras-MG, Brazil. Sixteen male and female dogs were used, of which eight were Beagles and eight were of other small to medium breeds, all of them were approximately 5± 2 years old and weighed 12,26±4,65kg. The experimental design was completely randomized, with four diet ary treatments (n=4). The experimental diets were: 1 - moist diet without addition of phosphate (control); 2 - moist diet with 0.3% sodium tripolyphosphate; 3 - moist diet with 0.3% sodium hexametaphosphate and 4 - moist diet with 0.3% sodium hexametaphosphate and 0.03% vitamin C. Prior to the start of the experiment, the dogs underwent dental prophylaxis. After an experimental period of 75 days, the dogs were examined for dental plaque, gingival sulcus measurement, and salivary pH.The oral health of these dogs was evaluated based on the labial surface of the canine teeth(C) and second (PM2), third (PM3) and fourth (PM4) premolars of the maxillary arch. Bacterial plaque measurement was done through digital photos by the GIMP 2 and ImageJ programs and the salivary pH was determined with pH indicator paper. The gingival sulcus was measured by means of a periodontal millimetric probe. The data were submitted to analysis of variance and means compared by the Scott-Knott test. There was a reduction (P <0.05) in canine bacterial plaques with dietary supplementation of hexametaphosphate, independent of vitamin C supplementation. There was no difference (P> 0.05) in gingival sulcus depth and salivary pH. It was concluded that inclusion of 0.3% hexametaphosphate in moist diets assists in the prevention of bacterial plaque accumulation in dogs.